ANALISIS KESULITAN BELAJAR MATEMATIKA MATERI PENGURANGAN BERSUSUN PADA SISWA KELAS 2 A SD NEGERI SUMBERMULYO - Pertiwi, Niken; Rofian; Cahyadi, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aims of this research are: (1) To find out students' difficulties in learning mathematics in grade 2 subtraction material at Sumbermulyo State Elementary School. (2) Identifying factors that influence mathematics learning difficulties in grade 2 subtraction material at Sumbermulyo State Elementary School. The type of research used is qualitative descriptive research, with the aim of describing, explaining and answering in detail the problem of mathematics learning difficulties in subtraction material and its causes. The data analysis method in this research has three flows that occur simultaneously with data reduction, data display, and conclusion verification. The research results show that students face several learning difficulties in mathematics subjects, especially in sequential subtraction material. These difficulties include determining the place value of a number, limitations in counting skills, and difficulty understanding processes, concepts, or solving mathematical problems, especially in the context of multiple subtraction. The causes of difficulties learning mathematics can be grouped into two main factors, namely internal factors and external factors. Internal factors include students' level of intelligence, students' attitudes towards learning, and students' learning motivation. Meanwhile, external factors include variations in teaching by teachers, learning methods and media used by teachers, as well as the condition of facilities and infrastructure in the classroom.